2022
DOI: 10.26434/chemrxiv-2022-cdt52
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insertion of Degradable Thioester Linkages into Styrene and Methacrylate Polymers

Abstract: The thionolactone 3,3-dimethyl-2,3-dihydro-5H-benzo[e][1,4]dioxepine-5-thione (DBT) is shown to homopolymerize and, for the first time, copolymerize with styrene and methacrylates, introducing degradable thioester backbone functionality. The rapid copolymerization with styrene was exploited to produce copolymers through free-radical polymerization in a starve-fed semi-batch setup. The copolymerization of DBT with tert-butyl methacrylate under RAFT conditions was hypothesized to involve selective retardation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 14 publications
(24 reference statements)
0
16
0
Order By: Relevance
“…[27][28][29][30][31] Thionolactones, such as dibenzo[c,e]oxepane-5-thione (DOT) have been recently presented as a degradable comonomer which undergo RROP with acrylates, acrylamides, acrylonitrile, [32][33][34][35] as well as vinyl esters, 36 styrene and methacrylates. 37,38 DOT is compatible with both FRP and RDRP and affords degradation via cleavage of the backbone thioester. Very recently, Guillaneuf et al used DOT in crosslinked systems and reported that a 3D-printed poly(pentaerythritol triacrylate) 39 and a poly(styrene-co-divinylbenzene) 38 both underwent degradation with 2 wt% and 5 mol% of DOT, respectively.…”
mentioning
confidence: 99%
“…[27][28][29][30][31] Thionolactones, such as dibenzo[c,e]oxepane-5-thione (DOT) have been recently presented as a degradable comonomer which undergo RROP with acrylates, acrylamides, acrylonitrile, [32][33][34][35] as well as vinyl esters, 36 styrene and methacrylates. 37,38 DOT is compatible with both FRP and RDRP and affords degradation via cleavage of the backbone thioester. Very recently, Guillaneuf et al used DOT in crosslinked systems and reported that a 3D-printed poly(pentaerythritol triacrylate) 39 and a poly(styrene-co-divinylbenzene) 38 both underwent degradation with 2 wt% and 5 mol% of DOT, respectively.…”
mentioning
confidence: 99%
“…72 A second generation thionobenzoate, 3,3-dimethyl-2,3dihydro-5H-benzo[e] [1,4]dioxepine-5-thione ( 14) with an ortho alkoxy substituent was shown to provide slightly better stabilisation of the intermediate radical and copolymerized, albeit sluggishly, with t-butylmethacrylate. 73 The thiocaprolactones 15 and 16, lacking the stabilisation of the intermediate radical by the aryl group, were shown to polymerize rapidly with the LAMs vinyl acetate, vinyl pivalate, and, though with retardation, N-vinylpyrrolidone. 70,74 Emerging applications of TARO-made copolymers exploit the fact that the backbone thioesters are weaker than (oxo) ester linkages available through conventional radical ring-…”
Section: Thiocarbonyl-addition Ring-opening (Taro) Polymerizationmentioning
confidence: 99%
“…Conversely, thiocarbonyl fluoride (F 2 CvS) and thiocarbonyl chlorofluoride (ClFCvS), which do not have β-bonds, undergo radical polymerization of the CvS bond, see Scheme 13A. 75 Although the thiocarbonyl Low rate; yields oligomers only Methyl acrylate 63 Thiocarbonyl species is incorporated at a faster rate than the vinyl comonomer mPEG acrylate 63,66,67 n-Butyl acrylate 68,69 t-Butyl acrylate 64 Acrylamide 66 Homopolymerization 73 Low yielding…”
Section: Radical Polymerization Of the Cvs Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29][30][31] Thionolactones, such as dibenzo[c,e]oxepane-5-thione (DOT) have been recently presented as a degradable comonomer which undergo RROP with acrylates, acrylamides, acrylonitrile, [32][33][34][35] as well as vinyl esters, 36 styrene and methacrylates. 37,38 DOT is compatible with both FRP and RDRP and affords degradation via cleavage of the backbone thioester by e.g. primary amines, strong bases or thiols.…”
mentioning
confidence: 99%